Reakcja chrząszczy szeliniaka sosnowca (Hylobius abietis L.) na insektycydy z grupy neonikotynoidów (chloronikotynyli) i fenylopirazoli - Malinowski, Henryk (Leśne Prace Badawcze, 2010)
The responses (knock-down and mortality) were studied of large pine weevil ( Hylobius abietis L.) adults to selected insecticides with different mechanisms of action, such as neonicotinoids (clothianidin, acetamiprid); acting on the nicotinic receptors of acetylcholine (ACh), and fenylpirazoles (fipronil); interfering with gamma butyric acid (GABA) receptors. Taking into account the speed of insect decay the order of effectiveness was as follows: the most effective insecticides were those that interfered with GABA receptors and second best insecticides acted on nicotinic receptors of ACh.